Association between maternal exposure to environmental endocrine disruptors and the risk of congenital heart diseases in offspring: a systematic review and meta-analysis - Kai Pan; Jie Xu; Chengxing Wang; Zhen Mao; Yuzhu Xu; Haoke Zhang; Jie Yu (Environmental Research Letters, 2024)
Congenital heart disease (CHD) is the most common type of congenital malformation and the leading cause of death in newborns. Some observational studies have investigated the relationship between exposure to environmental endocrine disruptors (EEDs) and CHD in pregnant women. However, the findings of epidemiological studies in different countries and regions remain controversial and exhibit significant variations. This meta-analysis aimed to explore the relationship between exposure to EEDs and CHD in pregnant women, hoping to provide some insights into related research in different regions and further demonstrate the relationship between the two. Three databases (PubMed, Embase, and Web of Science) were searched, and 17 studies with 1373 117 participants were selected, including 3 on polycyclic aromatic hydrocarbons (PAHs), 5 on pesticides/insecticides, 4 on phthalates, 4 on alkylphenolic compounds, and 7 on heavy metals. The Newcastle–Ottawa Scale was used to evaluate the quality of the studies. Begg’s and Egger’s tests were used to determine the publication bias of the studies, and the I ^2 statistics to evaluate the statistical heterogeneity among the studies. The adjusted estimates were pooled using the random-effects and fixed-effects models to explore the association between EEDs and CHD and its subtypes. Maternal exposure to PAHs [odds ratio (OR) = 1.34, 95% confidence interval (CI): 1.17–1.53)] (e.g. PAHs and tetralogy of Fallot, septal defects, and conotruncal defects)], pesticides/insecticides (OR = 1.32, 95% CI: 1.20–1.46), alkylphenolic compounds (OR = 1.46, 95% CI: 1.14–1.86), and heavy metals (arsenic, cadmium, mercury, and lead) (OR = 2.09, 95% CI: 1.53–2.86) during pregnancy was positively associated with CHD in offspring. This study found that exposure to EEDs in pregnant women was positively associated with CHD in offspring. These findings are of great significance for researchers to further study the relationship between the two.